The Impact of Cash Flow Management on Enhancing the Organizational Performance of Sustainable Industrial Projects. - Kadhim, Anfal Sameer; Khawam , Noor Riad (Indonesian Journal of Law and Economics Review, 2026)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:3be29ef7-980e-4bf6-81ca-d45659bf657a-4" data-testid="conversation-turn-2" data-scroll-anchor="false" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="8beee407-c8f4-4a7f-8ff4-397bc30e1c9b" data-message-model-slug="gpt-5-3" data-turn-start-message="true"> General Background: Contemporary industrial organizations operate in highly competitive environments requiring strong financial strategies to maintain performance and sustainability. Specific Background: Cash flow management is positioned as a central mechanism for maintaining liquidity, supporting operational continuity, and aligning financial planning with organizational goals in industrial settings. Knowledge Gap: Despite its importance, limited empirical evidence is available regarding how specific dimensions of cash flow management relate to organizational performance in sustainable industrial projects, particularly within Iraqi industrial contexts. Aims: This study examines the relationship between cash flow management and organizational performance of sustainable industrial projects, focusing on dimensions such as risk management, compliance, adaptability, strategic flexibility, financing deficit, surplus management, and future cash flow analysis. Results: Using a descriptive-analytical approach and survey data from 113 valid responses at the Kufa Cement Plant, findings reveal a significant correlation and contribution between cash flow management and organizational performance, measured through goals, profitability, and market share. Novelty: The study provides empirical evidence linking multidimensional cash flow management practices with performance outcomes in a real industrial setting. Implications: The findings support the need for structured cash flow strategies to sustain industrial operations, ensure financial stability, and strengthen long-term organizational performance in sustainable projects. Highlights: • Strong statistical relationship identified between financial liquidity practices and organizational outcomes • Empirical evidence derived from industrial sector data within a real operational environment • Multidimensional financial strategies linked to profitability, goals, and market positioning Keywords: Cash Flow Management, Organizational Performance, Sustainable Industrial Projects, Financial Strategy, Industrial Sector